Fantasies of Gender and the Witch in Feminist Theory and Literature - Sempruch, Justyna (Purdue University Press, 2008)
In her book Fantasies of Gender and the Witch in Feminist Theory and Literature, Justyna Sempruch analyses contemporary representations of the "witch" as a locus for the cultural negotiation of genders. Sempruch revisits some of the most prominent traits in past and current perceptions in feminist scholarship of exclusion and difference.